0300 Early Life Sleep Fragmentation Impairs Hippocampal-Dependent Learning and Sleep-Dependency in Hippocampal Calcium Transients. (25th May 2022) - Zamore, Zachary; Chou, Allison Tzu-Han; Schifman, Naomi; Fenik, Polina; Pullum, Keelee; Slinger, Michelle; Veasey, Sigrid
Abstract: Introduction: Sleep deprivation impairs hippocampal-dependent memory, and hippocampal-dependent memory impairments occur in some dementias, including Alzheimer's disease. As our population continues to age, understanding the molecular basis for memory impairments is increasingly important. We hypothesized that early life sleep fragmentation would result in lasting increases in hippocampal calcium transient activity. Methods: B6 mice were randomized to 12wk of sleep fragmentation or rested control conditions at age 8wk. Mice were microinjected with AAV9-CamKII-GCamp6F into the hippocampus and later implanted with a GRIN Lens into CA1 secured to a baseplate along with chronic EEG/EMG electrodes and recording connector. Calcium recordings were obtained two to three months after injection and recordings were obtained across sleep-wake cycles>4mins of wake and NREM sleep. Individual cells across animal were combined into sleep fragmented (n = 521 cells) or rested (n = 443 cells) groups during wake or sleep. Average FFx was analyzed by group and condition by T-tests, paired for within and unpaired across groups. A spatial object recognition assay was also performed on all mice (n=16 for both groups) and performance across group was analyzed by paired T-tests. Results: Rested mice showed normal spatial object recognition (n = 16, p<0.05). In contrast, SF mice showed impaired spatial object recognition (n = 16, N.S.). There were no differences across sleep conditions in calcium transient FFx for waking (p>0.05). However, in sleep, cells in SF mice had significantly higher average FFx values than cells in rested mice (p<0.0001). Conclusion: Early-life sleep fragmentation has long-lasting impacts on memory. Since spatial memory is dependent on hippocampal function, the calcium transient FFx data suggests that a driver of this hippocampal memory impairment may be higher firing rates in sleep and/or greater calcium exposure in hippocampal CamKII neurons in sleep, both of which may perturb microglial maintenance of synapses. Understanding the molecular drivers behind this calcium dysfunction will be essential in our understanding of neurodegeneration, dementia, and Alzheimer's disease. Support (If Any): NIH AG054104; AG064231